Photorefractive optics materials, properties, and applications - Yin, Shizhuo, 1963-; Yu, Francis T. S., 1932-
A reference both for technical and non-technical staffs who are interested in photorefractive optics. This book covers the development in materials, phenomena, and applications; includes growth, characterization, dynamic gratings, and liquid crystal PR effect; and provides the overall picture of trends in photorefractive optics.